Cover Jurnal Fitopatologi Vol. 17 No. 5, September 2021 (Jurnal Fitopatologi Indonesia, 2022)
This editorial contains the front cover, editorial page, and back cover of the Indonesian Journal of Phytopathology, Vol. 17 No. 5, September 2021